Manželské etudy – 4. Zuzana a Stanislav . Marriage Stories – 4. Zuzana and Stanislav - Třeštíková, Helena (Beckov, Anna, 1987)
Duration: 00:35:00 Zuzka and Standa had to get married. She hadn’t graduated from high school; he was an electrical engineer but only one year older then her. Due to the difficult housing conditions that existed in Czechoslovakia, they began living together almost three years after they were married and even though they already had two children. The immaturity with which they entered into marriage, combined with their very different characters soon took its toll.